The Constitution of Cádiz, elections and municipalities - Andújar Moreno, Jorge (2011)
This year (2012) we are celebrating the bicentennial of the Constitution of Cadiz, the first and only political chart of the Spanish monarchy that considered those born in both hemispheres as citizens with equal rights, including creoles, indians and mestizos and even the illiterate. Similarly, the reformist and liberal character of the Constitution of Cadiz enabled the punishment of a number of human liberties and rights, which would be included in all of the following Peruvian Constitutions, thereby constituting its natural point of reference. The acknowledgement of the people as a source of sovereignty led to the first municipal and parliamentary elections, thereby establishing the discipline of Electoral Law. This article highlights the importance and the historical autonomy of the municipalities, transferred from Spain to Peru and which existed long before in Rome, reflecting on its constitutional evolution and on the fact that despite their solemn acknowledgement in some magna cartas — such as the Cadiz Constitution — this has not guaranteed their fulfillment.